2014
DOI: 10.1165/rcmb.2013-0300oc
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor-1 Deficiency Augments Visceral Mesothelial Organization, Intrapleural Coagulation, and Lung Restriction in Mice with Carbon Black/Bleomycin–Induced Pleural Injury

Abstract: Local derangements of fibrin turnover and plasminogen activator inhibitor (PAI)-1 have been implicated in the pathogenesis of pleural injury. However, their role in the control of pleural organization has been unclear. We found that a C57Bl/6j mouse model of carbon black/bleomycin (CBB) injury demonstrates pleural organization resulting in pleural rind formation (14 d). In transgenic mice overexpressing human PAI-1, intrapleural fibrin deposition was increased, but visceral pleural thickness, lung volumes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
136
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(144 citation statements)
references
References 34 publications
8
136
0
Order By: Relevance
“…Recently, we reported that expression of tissue factor pathway inhibitor is phosphatidylinositol-3-kinase (PI3K)/Akt and NF-B dependent and that these signaling pathways are linked in HPMCs (19). We therefore inferred that PI3K/Akt/NF-B signaling could contribute to the progression of MesoMT, a possibility further supported by prior reports linking these pathways to mesenchymal transition in alternative cell types (10,15,18).…”
supporting
confidence: 65%
See 4 more Smart Citations
“…Recently, we reported that expression of tissue factor pathway inhibitor is phosphatidylinositol-3-kinase (PI3K)/Akt and NF-B dependent and that these signaling pathways are linked in HPMCs (19). We therefore inferred that PI3K/Akt/NF-B signaling could contribute to the progression of MesoMT, a possibility further supported by prior reports linking these pathways to mesenchymal transition in alternative cell types (10,15,18).…”
supporting
confidence: 65%
“…Our work and that of others has shown that pleural mesothelial cells (PMCs) contribute to the progression of PF by undergoing a process called mesothelial (Meso) mesenchymal transition (MT) (1,2,13,14,19), through which PMCs assume characteristics of myofibroblasts. Mesothelial MT (MesoMT) is characterized by mesenchymal changes in cell morphology.…”
mentioning
confidence: 69%
See 3 more Smart Citations